Cerebral ischemia and calcium: [International Symposium Cerebral Ischemia and Calcium, held in Prien/Chiemsee, Federal Republic of Germany, in June 1988] - Hartmann, Alexander; Kuschinsky, Wolfgang (Springer Berlin Heidelberg, 1989)
Although many books deal with isolated problems of calcium disturbance in relation to cardiac and cerebral function, this is the first to focus specifically on calcium metabolism and cerebral ischemia. Internationally acknowledged experts present recent data and new concepts in an interdisciplinary approach to the subject. They examine basic information on the pathophysiology of cellular events, the damage caused by excitotoxic substances, and the effects of calcium antagonistic drugs as measured in experimental animals. These contributions may help lead to possible therapeutic interference for the prevention of calcium imbalance
Keywords: Konferenzschrift -- 1988 -- Prien, Chiemsee; Calciumantagonist; Ischämie; Hirnkrankheit